DIGITAL-BASED MONITORING OF THE FULFILLMENT OF VOTING RIGHTS FOR PERSONS WITH DISABILITIES IN THE 2024 MEDAN CITY REGIONAL HEAD ELECTIONS - Hadita, Cynthia; Anshari Sibarani, Fauzi; Akbar Simatupang, Rajarif Syah (NOMOI Law Review, 2025)
Fulfillment right choose for person with disabilities disability is an integral part of inclusive democracy , but in practice Still often experience obstacles , good from side accessibility information , infrastructure , and mechanism participation in the political process . Research This leave from problem lack of oversight and transparency in fulfillment right political disability in elections Head of Medan City Region in 2024, where the limitations manual mechanisms often give rise to data bias and potential neglect rights . Purpose study This is analyze effectiveness monitoring digital -based as instrument For ensure participation political disability can protected and guaranteed optimally . Method research used is approach juridical-empirical with technique data collection through studies library , interview with voters disability , organizer elections , as well as observation supported fields utilization application digital monitoring . Research results show that monitoring digital -based capable increase transparency , data accuracy , and give room more participation wide for person with disabilities disability . However Thus , it was found challenge in the form of limitations digital literacy , internet networks , and Not yet integration system digital surveillance with regulations elections . Therefore that , innovation technology need strengthened through policy responsive law for democracy inclusive truly can realized.